Strengthening Financial Literacy Based on the Values of KH. Hasyim Asy'ari:: A Community Service Program for Indonesian International Students - Haryanti, Peni; Sopingi, Imam; Hidayati, Athi’; Musfiroh, Anita; Yuni K, Kusnul Ciptanila; Laili, Choirun Nisful (Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This community service program (PKM) aimed to improve financial literacy among Indonesian international students at Al-Azhar University in Cairo by integrating the ethical values of KH. Hasyim Asy'ari—tawazun (balance), ta'awun (cooperation), and itiqad (integrity). The program was conducted online via Zoom in March–May 2026, involving 45 participants across two structured sessions using the Participatory Action Research (PAR) combined with a Values-Based Financial Education (VBFE) approach. Results showed a significant improvement in financial literacy scores, with the overall mean increasing from 55.6 (pre-test) to 82.3 (post-test), reflecting a 48% gain (Cohen's d = 2.21). Improvements were recorded across all five dimensions, with remittance management showing the highest increase. The integration of Islamic ethical values proved effective as a cultural bridge enhancing both cognitive understanding and ethical financial behavior. Participants demonstrated strong potential as financial literacy change agents upon returning to Indonesia.